Effects of Six‐Membered Carbohydrate Rings on Structure, Stability, and Kinetics of G‐Quadruplexes. Issue 43 (11th September 2013) - Zhou, Jun; Abramov, Michael; Liu, Fengwu; Amrane, Samir; Bourdoncle, Anne; Herdewijn, Piet; Mergny, Jean‐Louis
Abstract We have evaluated the conformational, thermal, and kinetic properties of d(TGGGGT) analogues with one or five of the ribose nucleotides replaced with the carbohydrate residues hexitol nucleic acid (HNA), cyclohexenyl nucleic acid (CeNA), or altritol nucleic acid (ANA). All of the modified oligonucleotides formed G‐quadruplexes, but substitution with the six‐membered rings resulted in a mixture of G‐quadruplex structures. UV and CD melting analyses showed that the structure formed by d(TGGGGT) modified with HNA was stabilized whereas that modified with CeNA was destabilized, relative to the structure formed by the unmodified oligonucleotide. Substitution at the fourth base of the G‐tract with ANA resulted in a greater stabilization effect than substitution at the first G residue; substitution with five ANA residues resulted in significant stabilization of the G‐quadruplex. A single substitution with CeNA at the first base of the G‐tract or five substitutions with HNA resulted in striking deceleration or acceleration of G‐quadruplex formation, respectively. Our results shed light on the effect of the sugar moiety on the properties of G‐quadruplex structures.